Negative Short-Term Outcome of Detoxification Therapy in Chronic Migraine With Medication Overuse Headache: Role for Early Life Traumatic Experiences and Recent Stressful Events - Bottiroli, Sara; Galli, Federica; Viana, Michele; De Icco, Roberto; Bitetto, Vito; Allena, Marta; Pazzi, Stefania; Sances, Grazia; Tassorelli, Cristina (Frontiers in Neurology, 2019)
Background: Early traumatic experiences and Stressful episodes appear to be associated to the development and perpetuation of chronic pain disorders and to dependence-related behaviors. Objective: The present study evaluated whether these factors can be predictors, together with psychiatric conditions, of the outcome of a detoxification treatment in patients suffering from chronic migraine and medication-overuse headache in a 2-month follow-up. Methods: Consecutive patients undergoing a detoxification program as therapy for treating chronic migraine and medication overuse headache at the Pavia Headache Center were analyzed. During this program, lasting about one week, all patients received the standard CARE in-patient withdrawal protocol, which consisted in discontinuing abruptly the overused drug(s) and receiving daily detoxification therapy. Data on childhood traumatic events and recent stressful ones were analysed by means of the Childhood Trauma Questionnaire and Stressful life-events Questionnaire. Psychiatric conditions were evaluated using the Structured Clinical Interview for Diagnostic and Statistical Manual of mental disorders. Results: A total of 166 (80% females; mean age 44.7) patients completed the follow-up at 2 months after the detoxification program: 118 (71%) (78% females; mean age 44.7) stopped overuse and reverted to an episodic pattern of headache (Group A); 19 (11%) (89% females; mean age 41.3) kept overusing and maintained a chronic pattern of headache (Group B); and 29 (18%) (79% females; mean age 46.9) stopped overuse without any benefit on headache frequency (Group C). At the multivariate analyses, a higher number of early life emotional distress (Odds Ratio 11.096; p = 0.037) arose as a prognostic factor for the outcome in Group B, while major depression during life-time (Odds Ratio 3.703; p = 0.006) and higher number of severe stressful episodes in the past 10 years (Odds Ratio 1.679; p = 0.045) were prognostic factors for the outcome of Group C. Conclusions: Data suggest that early life traumas and stressful events have a negative impact on the outcome of the detoxification program in subjects overusing acute medication for headache. The history of emotional childhood traumas is associated to the failure to cease overuse, whereas recent very serious life events are associated to the persistence of headache chronicity.